(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article reveals the ideas of Fitrat, a well-known representative of the Jadid movement, about the need for youth educated in Jadid schools to implement reforms in the country, and to include the country among the ranks of developed countries. The importance of using the creative ideas of contemporaries in the development of the spiritual and educational sphere in our New Uzbekistan and building the foundations of the III Renaissance is emphasized.